Cervical esophageal perforation in a diabetic elderly - Ana María Nazario Dolz; Sergio Hernández Cumbá; Joel Pineda Chacón (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 67 years patient with a history of diabetes mellitus is described who had eaten a fish bone 4 days ago and went to "Saturnino Lora Torres" Teaching Clinical Surgical Provincial Hospital emergency room in Santiago de Cuba, due to disphony, disphagia for liquids, neck functional impotence and a 38 ºC fever.  He had the diagnosis of an esophageal perforation in the cervical region, so he was admitted and operated as an emergency; 6 days later he underwent surgery again to check the cervicotomy and to carry out the opening of a septic fasciitis in the right side of the thorax.  The patient had a satisfactory clinical course and he was discharged 35 days later.